2023
DOI: 10.3389/fpls.2023.1160535
|View full text |Cite
|
Sign up to set email alerts
|

Plastome evolution and phylogenomics of Trichosporeae (Gesneriaceae) with its morphological characters appraisal

Abstract: Trichosporeae is the largest and most taxonomically difficult tribe of Gesneriaceae due to its diverse morphology. Previous studies have not clarified the phylogenetic relationships within this tribe on several DNA markers, including the generic relationships within subtribes. Recently, plastid phylogenomics have been successfully employed to resolve the phylogenetic relationships at different taxonomic levels. In this study, plastid phylogenomics were used to explore the relationships within Trichosporeae. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The phylogenetic analysis, which is displayed in Figure 3 , demonstrated that a well-supported lineage (BS = 100%) exclusively comprising all Hemiboea species and the topology within Hemiboea is consistent with previous findings (Cui et al. 2023 ). Within Hemiboea , H. pterocaulis was identified as the strong supported sister to H. suiyangensis (BS = 100%), and this clade, in turn, formed the sister group to H. yongfuensis , with strong support (BS = 100%).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The phylogenetic analysis, which is displayed in Figure 3 , demonstrated that a well-supported lineage (BS = 100%) exclusively comprising all Hemiboea species and the topology within Hemiboea is consistent with previous findings (Cui et al. 2023 ). Within Hemiboea , H. pterocaulis was identified as the strong supported sister to H. suiyangensis (BS = 100%), and this clade, in turn, formed the sister group to H. yongfuensis , with strong support (BS = 100%).…”
Section: Resultssupporting
confidence: 89%
“…The following sequences were used: H. pterocaulis OR195434 (in this study); H. malipoensis NC_080279, H. sinovietnamica NC_079572, H. purpurea NC_080277, H. subacaulis NC_080278, H. purpureotincta NC_080281, H. integra NC_079574, H. suiyangensis NC_080282, H. yongfuensis NC_079573, H. ovalifolia NC_054358, H. parvibracteata NC_080280, H. fangii NC_079575 (Cui et al. 2023 ). Outgroups: O. argyreia var.…”
Section: Resultsmentioning
confidence: 99%